Roller derby's publicness: toward greater recognition of diverse genders and sexualities in the Bible Belt. Issue 4 (2nd April 2016) - Sheehan, Rebecca; Vadjunec, Jacqueline M.
Abstract : While scholars have considered the various meanings of roller derby for participants and discussed how roller derby critiques and stabilizes gender and sexuality normativity, their investigation into how a larger public is impacted by roller derby's public performances has received less attention. Here, we begin to address this oversight. Employing both participant and spectator data, we examine facets of publicness in the discursive and material spatial practices associated with roller derby in the US Bible Belt, specifically Oklahoma. While some scholars doubt that there is much social impact from roller derby, we suggest that the specific spatial qualities in roller derby's public performances, in both the sporting and playful senses, contribute to a change in cultural norms – that of greater recognition of diverse genders and sexualities in this region. Such validation increases the social stability of individuals who do not neatly reside within heteronormativity.